Impacts of elasticity and porosity of the channels on the performance features of thermoelectric module mounted system and efficient computations with multi-proper orthogonal decomposition approach - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Doranehgard, Mohammad Hossein (Elsevier, 2021)
Effects of wall elasticity and porosity of the channel on the performance characteristics of TEG module integrated system are explored numerically with finite element method. A porous layer in the lower channel is introduced with hybrid nanoparticles in the fluid. Effects of different values of elastic modulus of the top and bottom channel walls (5 & times;103 <= E1,& nbsp;E2 & nbsp;<=& nbsp;1010), Darcy number (5 & times;10 & minus;4 & nbsp;<=& nbsp;Da & nbsp;<=& nbsp;5 & times;10 & minus;1), porous layer height (0.2H & nbsp;<=& nbsp;py & nbsp;<=& nbsp;0.8H) and length in flow direction (0.25L & nbsp;<=& nbsp;px & nbsp;<=& nbsp;0.85L), Reynolds number (200 & nbsp;<=& nbsp;Re & nbsp;<=& nbsp;1000) and hybrid nanoparticle volume fraction (0 & nbsp;<=phi <=& nbsp;2%) on the convection and power generation are analyzed. The presence of elastic walls may affect the flow field in local regions but the overall impact on the power variation is slight while 2.8%& nbsp;variation is obtained. The presence of the porous layer altered the power generation features while increasing the permeability and height of the porous layer resulted in higher thermoelectric power generation. The increment amounts are 32%& nbsp;for the highest permeability and 17%& nbsp;for the highest porous layer height. The length of porous layer in the flow direction has slight impact on power generation features while introducing nano-sized particles further enhanced the power by about 15%& nbsp;at the highest & nbsp;phi. The computational cost of generated power is drastically reduced from 2.5 h for full coupled model to two minutes by using a multi-POD approach.& nbsp; (c) 2021 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Thermoelectric; Porous media; Elastic walls; Hybrid nanofluid; Finite element method; Multi-POD